Controllable, eco-friendly, synthesis of highly crystalline 2D-MoS2 and clarification of the role of growth-induced strain. (13th June 2018) - Michail, Antonios; Parthenios, John; Anestopoulos, Dimitris; Galiotis, Costas; Christian, Meganne; Ortolani, Luca; Morandi, Vittorio; Papagelis, Konstantinos
Abstract: A controlled and eco-friendly, scalable CVD method for the production of single and few layer MoS2 crystals is proposed. The MoS2 crystals are fabricated at atmospheric pressure through the reaction of pre-deposited sodium molybdate (Na2 MoO4 ) in solution and elemental sulfur at 800 °C, offering the flexibility to achieve two growth regimes -either homogeneously distributed single layer MoS2 crystals or continuous MoS2 films- by varying the Na2 MoO4 solution concentration. In particular, for low precursor concentrations, isolated single layer MoS2 crystals with controllable mean lateral size were produced. Higher concentrations resulted in continuous single layer films grown in tandem with highly oriented few layer epitaxial domains. The area of the monolayer relative to the few-layer domains can be adjusted. The significant impact on the optical properties of single layer MoS2 crystals due to the growth induced strain is also examined. The grown monolayer crystals are found to experience ~0.3% biaxial tensile strain relative to the exfoliated ones, while a strain relief of 0.6% is measured when these CVD crystals are transferred to another plastic substrate. Moreover, in their photoluminescence (PL) spectra, the neutral exciton and negative trion peaks are shifted linearly with biaxial strain. By correlating PL and Raman spectroscopies the deformation potential of the direct optical transition in single layer MoS2 can be determined.